Free fatty acid receptor-2 activate to promote experimental acute and chronic ileitis in rats - Zherebiatiev, А. S.; Spivak, M. A.; Kamyshnyi, A. M.; Камишний, Олександр Михайлович (Запорізький державний медичний університет, 2015)
Background and aim. Short-chain fatty acids (SCFAs), the most abundant microbial metabolites in the intestine, activate cells via free fatty acid receptor-2 (FFAR2). FFAR2 is highly expressed on immune cells, and several studies suggest that the receptor plays a role in inflammatory bowel disease (IBD). We studied of FFAR2 mRNA expression in the inflamed ileum of rats with experimental ileitis.